The Role of Online Aggregators in The Vegetable Value Chain - Janita Meliala; Musa Hubeis; Siti Jahroh; Agus Maulana (Jurnal Manajemen & Agribisnis, 2020)
In Indonesia, many intermediaries of agricultural products are emerging as modern actors called business aggregators who utilize information from the internet or online technologies in their business activities. This study aims to analyze the activities and roles of online aggregators (based on information technology) in the order of value chains of agricultural products, especially vegetables. Purposive sampling technique was used in selecting 12 online business aggregators of vegetable products. Data were obtained through Focus Group Discussions and in-depth interviews with the business aggregator online owner. Based on the results of the analysis show that the main activities of the aggregator business value chain that are divided into three value chains, namely input provider, processing and marketing providers. Online aggregators become important actors in the agribusiness system in the future. In conventional agribusiness systems, non-online aggregators, whose position is in the subsystem, downstream agribusiness, but in online aggregator at present with the advancement of internet, the aggregator is in the middle/middle, between upstream, cultivation, downstream and supporting institutions subsystems. Keywords: intermediaries, online aggregator, vegetable products, value chain